Overview of the construction of geothermal doublets in Poland - Noga, Bogdan (Instal, 2023)
This paper presents the types of geothermal doublet construction performed in Poland. An analysis was made of a geothermal doublet consisting of two vertical wells, a vertical well and a directional well with a „J” type trajectory and a vertical well and a directional well with an „S” type trajectory. The offset of the thermal water inlet of the directional well from the outlet of the vertical well was determined. This distance depends mainly on the depth of the wells in the geothermal doublet – the deeper the wells, the greater the distance between the bottoms of the two wells. In Poland, there are currently 12 geothermal doublets (extractor well and absorption well) or multiples thereof comprising 34 geothermal wells, including: 25 vertical wells, 6 directional wells with an ‚S’ type trajectory, and 3 directional wells with a ‚J’ type trajectory.
Keywords: geothermal; geothermal installation; geothermal well; extraction well; absorption well; directional well type “J”; directional well type “S”